The Relationship of Knowledge and Attitudes Towards Community Waste Management in Baranti District, Sidenreng Rappang Regency - Firdaus Daud; Muhammad Junda (Universitas Negeri Makassar, 2023)
Abstract. Correlation of Knowledge and Attitudes towards Waste Management in the Community in Baranti Subdistrict in Sidenreng Rappang District. The type of this study is expost-facto, which aims to discover the correlation between knowledge and attitudes towards waste management in the community in Baranti subdistrict in Sidenreng Rappang district. The independent variables are knowledge and attitudes, whereas the dependent variables are the waste management. The research population in this study were all households in the Baranti subdistrict in Sidenreng Rappang district, whereas the samples were 190 people taken by using the Issac and Michael table with the level of error 5%. Data collection technique employed questionnaire and interviews. Data were analyzed by employing descriptive statistical technique and inferential statistical technique. The results of the study based on inferential statistics analysis are as follows, it is that there is a positive and significant correlation between knowledge and waste management at a strong correlation level with the sig. there is a positive and significant correlation between attitudes and waste management at a very strong correlation level with the sig. There is a positive and significant correlation between knowledge and attitudes towards community waste management at a very strong correlation level with the sig. The biggest effective contribution to the dependent variable (Waste Management) is given by attitude by 55.81%, and knowledge by 16.23%. The total effective contribution is 72.04%, which means knowledge and attitude collectively provides an effective contribution by 72.04% to the community waste management in Baranti subdistrict in Sidenreng Rappang district, while 27.96% is influenced by unexamined factors.Keywords: knowledge, attitudes, waste management